Pre - and post-emergent application effects of nemarioc-ag phytonematicide of growth of potato and suppression of meloidogyne incognita - Sefefe, Selaelo Khutso (University of Limpopo, 2019)
Damage and significant losses of potato cultivar due to Meloidogyne incognita has become a serious challenge, after the withdrawal of synthetic chemical nematicides due to their environment-unfriendliness. Various alternatives have been investigated each with a wide range of drawbacks. Most phytonematicides were highly phytotoxic to crops, while their effects on nematode suppression were highly variable. The use of Nemarioc-AG phytonematicide at pre- and post-emergence would help in determining the level that is effective in supressing M. incognita without being phytotoxic. The objective of this study was to determine whether Nemarioc-AG phytonematicide could serve as pre- and post-emergent phytonematicide without inducing phytotoxicity while suppressing population densities of M. incognita. For achieving this objective, treatments, namely, 0, 2, 4, 8 and 16 g of Nemarioc-AG phytonematicide, were arranged in a randomised complete block design (RCBD), with 7 replicates. Potato seed tubers were sown into 20 cm pots, Nemarioc-AG phytonematicide placed above the tubers and covered with soil, after initiation of treatments 5 000 eggs and second stage juveniles (J2) of M. incognita per plant were inoculated. For post-emergent, treatments, replications and design were the same as in pre-emergent. Potato seed tubers were sown and inoculated with 5000 eggs and second-stage juveniles (J2) of M. incognita per plant after 100% emergence. Nemarioc-AG phytonematicide were applied 7 days after inoculation. Trials were conducted in autumn (February-April) 2017 (Experiment 1) and repeated in autumn 2018 (Experiment 2). Plant growth variables and selected nutrient elements were collected and analysed using the Curve Fitting Allelochemical Response Data (CARD) model and lines of best fit, respectively. In pre-emergent application, Experiment 1, MCSP was established at 1.95 g, with the overall xii sensitivity (∑k) being equal to zero. Therefore, in Experiment 1 and Experiment 2, all nutrient elements to increasing concentration of Nemarioc-AG phytonematicide exhibited negative quadratic relations. In both Experiments, nematode variables over increasing concentration of Nemarioc-AG phytonematicide on potato exhibited negative quadratic relations, except in Experiment 1, where J2 in roots exhibited positive quadratic relations, with models ranging between 72 to 99%. In post emergent, Experiment 1, MCSP was established at 1.57 g, with the overall sensitivity (∑k) being equal to 2. In Experiment 1 and Experiment 2, nutrient elements over increasing concentration of Nemarioc-AG phytonematicide exhibited positive and negative quadratic relations, with models ranging from 89 to 97%. In Experiment 1, nematode variables over increasing concentration of Nemarioc-AG phytonematicide exhibited negative quadratic relations, with models ranging between 92 and 98%. Positive and negative relations suggested that the product stimulated and inhibited plant growth or accumulation of selected essential nutrient elements, respectively. Increasing concentration of Nemarioc-AG phytonematicide had stimulated certain plant variables and inhibited population densities of M. incognita in pre- and post emergent application; therefore, this product was suitable for use as pre- and post emergent in management of nematodes on the test crop.
Thesis (M. Agric. (Plant Protection)) -- University of Limpopo, 2019
Keywords: Root-knot nematode; Meloidogyne incognita; Potato cultivar; Northern root-knot nematode; Peanut root-knot nematode